ORGANIZED ECOLABELLING: NORTH-SOUTH IMPLEMENTATION OF “KICKING AWAY THE LADDER” (CASE: PALM OIL TRADE BETWEEN INDONESIA AND EUROPE) - Nanda Kartika Ayu (UIN ALAUDDIN MAKASSAR, 2020)
Liberalization is one of the theis that is expected to be able to answer the acceleration and development of the economy of developing countries. One element of liberalization is market openness that will make developing countries unite with global markets both in accepting investments or trading in exports and imports. However, along with the development of technology, the demand for the North (developed countries) in carrying out its trade began to implement an